The Role of Decision Theory in Improving Team Performance in the Work Environment - Rahmawati S, Elia; Masyithah N, Rachmadani; Fatrecia S, Erika; Hidayat N, Rusdi; Kusumasari, Indah Respati (Indonesian Journal Publisher, 2024)
This research aims to analyze the role of decision-making theory in improving team performance in the work environment. Using a literature study approach, this research explores how the application of decision-making theories can influence team effectiveness as well as the factors that support team performance through appropriate decision-making. The results revealed that the application of structured and data-driven decision-making can strengthen teamwork, improve communication, and minimize internal conflicts, which ultimately contribute to improving the productivity and quality of team performance. Various decision-making theories, such as rational decision theory and consensus-based decision models, provide clear guidelines for making more informed and efficient decisions. This research also highlights the importance of emotional engagement, team member motivation, and the application of decision models that suit team and organizational dynamics. Overall, effective decision-making is key to achieving organizational goals, as it can improve team performance, productivity, and member job satisfaction. Therefore, training on decision-making in the work environment is essential to support team and organizational success.